A cryptic plastid and a novel mitochondrial plasmid in Leucomyxa plasmidifera gen. and sp. nov. (Ochrophyta) push the frontiers of organellar biology - Dovilė Barcytė; Karin Jaške; Tomáš Pánek; Tatiana Yurchenko; Tereza Ševčíková; Anežka Eliášová; Marek Eliáš (Open Biology)
Complete plastid loss seems to be very rare among secondarily non-photosynthetic eukaryotes. Leukarachnion sp. PRA-24, an amoeboid colourless protist related to the photosynthetic algal class Synchromophyceae (Ochrophyta), is a candidate for such a case based on a previous investigation by transmission electron microscopy. Here, we characterize this organism in further detail and describe it as Leucomyxa plasmidifera gen. et sp. nov., additionally demonstrating it is the first known representative of a broader clade of non-photosynthetic ochrophytes. We recovered its complete plastid genome, exhibiting a reduced gene set similar to plastomes of other non-photosynthetic ochrophytes, yet being even more extreme in sequence divergence. Identification of components of the plastid protein import machinery in the L. plasmidifera transcriptome assembly corroborated that the organism possesses a cryptic plastid organelle. According to our bioinformatic reconstruction, the plastid contains a unique combination of biosynthetic pathways producing haem, a folate precursor and tocotrienols. As another twist to its organellar biology, L. plasmidifera turned out to contain an unusual long insertion in its mitogenome related to a newly discovered mitochondrial plasmid exhibiting unprecedented features in terms of its size and coding capacity. Combined, our work uncovered further striking outcomes of the evolutionary course of semiautonomous organelles in protists.